Effectiveness of eight or more antenatal contacts on health facility delivery and early postnatal care in low- and middle-income countries: a propensity score matching - Chilot, Dagmawi; Aragaw, Fantu Mamo; Belay, Daniel Gashaneh; Asratie, Melaku Hunie; Merid, Mehari Woldemariam; Kibret, Anteneh Ayelign; Teshager, Nahom Worku; Alem, Adugnaw Zeleke (Frontiers in Medicine, 2023)
Background: Despite progress in reducing maternal and child mortality, many low and middle-income countries (LMICs) still experience an unacceptably high level of the problem. The World Health Organization (WHO) recently recommended pregnant women should have at least eight antenatal care visits (ANC8+) with a trained healthcare provider as a key strategy to promote pregnant women's health. Antenatal care is an imperative factor for subsequent maternal health care utilization such as health facility delivery and early postnatal care (EPNC). This study aimed to examine the net impact of ANC8+ visits on health facility delivery and EPNC in LMICs by using a propensity score matching analysis. Methods: We used the recent Demographic and Health Survey (DHS) datasets from 19 LMICs. Women of reproductive age (15-49 years) who had given birth within one year preceding the survey were included. A propensity score matching analysis was employed to assess the net impact of eight or more antenatal care visits on health facility delivery and early postnatal care. Result: After matching the covariates, women who attended ANC8+ visits had a 14% (ATT=0.14) higher chance to give delivery at health facilities compared to women who attended less than 8 ANC visits. This study further revealed that women who had ANC8+ visits were associated with a 10% (ATT=0.10) higher probability of early PNC compared to their counterparts. Conclusions and recommendations: This study confirmed that ANC8+ visits significantly increased the likelihood of health facility-based delivery and early PNC utilization in LMICs. These findings call for public health programs to focus on pregnant women attending adequate ANC visits (according to revised WHO recommendation) as our study indicates that ANC8+ visits significantly improved the chances of subsequent care. Keywords: Antenatal care; Health facility delivery; Propensity score matching, LMICS